Early Christian lives : life of Antony by Athanasius, life of Paul of Thebes by Jerome, life of Hilarion by Jerome, life of Malchus by Jerome, life of Martin of Tours by Sulpicius Severus, life of Benedict by Gregory the Great /: life of Antony by Athanasius, life of Paul of Thebes by Jerome, life of Hilarion by Jerome, life of Malchus by Jerome, life of Martin of Tours by Sulpicius Severus, life of Benedict by Gregory the Great. (1998) - Unknown
No abstract available